Nuclear translocation of spike mRNA and protein is a novel feature of SARS-CoV-2 - Sattar, Sarah; Kabat, Juraj; Jerome, Kailey; Feldmann, Friederike; Bailey, Kristina; Mehedi, Masfique (Frontiers in Microbiology, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes severe pathophysiology in vulnerable older populations and appears to be highly pathogenic and more transmissible than other coronaviruses (Liu et al., 2020;Osan et al., 2022). The spike (S) protein appears to be a major pathogenic factor that contributes to the unique pathogenesis of SARS-CoV-2. Although the S protein is a surface transmembrane type 1 glycoprotein, it has been predicted to be translocated into the nucleus due to the novel nuclear localization signal (NLS) “PRRARSV”, which is absent from the S protein of other coronaviruses. Indeed, S proteins translocate into the nucleus in SARS-CoV-2-infected cells. S mRNAs also translocate into the nucleus. S mRNA colocalizes with S protein, aiding the nuclear translocation of S mRNA. While nuclear translocation of nucleoprotein (N) has been shown in many coronaviruses, the nuclear translocation of both S mRNA and S protein reveals a novel feature of SARS-CoV-2.